The evolution of the luminosity function faint end of cluster galaxies in the Cluster-EAGLE simulation. Issue Volume 14:Issue S344(2019) (August 2018) - Negri, Andrea; Vecchia, Claudio Dalla; Aguerri, Alfonso; Bahé, Yannick; Barnes, David; Kay, Scott
Abstract: In the last decade observations have been able to probe the evolution of the galaxy luminosity function, in particular showing a variation of its faint-end with redshift. We employ the data of the Cluster-EAGLE project, a set of cosmological, hydrodynamical zoom-in simulations of 30 galaxy clusters, to study the evolution of the galaxy luminostity functions in clusters with redshift. We compile a catalogue of simulated galaxies' luminosities in the SDSS bands using the E-MILES spectra database, and taking into account dust attenuation. Stacked luminosity functions present little evolution with redshift of the faint-end slope from z=3.5 to z=0, regardless of the cluster mass.